Post-Fire seed bank in a Xerophytic shrubland - Martinez Orea, Y.=700 1 Castillo Arguero, S.; Guadarrama Chavez, M.P.; Sanchez, I.
(Es, En)
Ilus., 59 ref.
Keywords: BANCO DE GENES; FUEGO; MATORRAL; MEXICO; MATORRAL XEROFILO; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO